Rancang Bangun Aplikasi Display Multimedia Dengan Fitur Kreasi Konten Interaktif Berbasis Augmented Reality - Roedavan, Rickman; Leman, Abdullah Pirus (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2025)
Bandung Techno Park (BTP) is one of Telkom University's innovation showcases frequently visited by students from both Indonesia and other countries such as Malaysia and Korea. However, BTP faces challenges in providing multimedia displays that effectively attract attention and offer interactive experiences for visitors. To address this issue, this study develops ARMazing, an Augmented Reality (AR)-based multimedia application designed to display various 3D animals in both realistic and cartoon forms. The research methodology includes literature review, system design based on the Multimedia Development Life Cycle (MDLC) model, and user testing and evaluation through a survey of 43 BTP visitors. The application features a creation mode, allowing users to select virtual animals, take photos, and record videos with them. Survey results indicate a positive response, with 83.2% of respondents appreciating the visual design, 81.4% valuing the educational content on animal species, and 90.7% enjoying the content creation feature. Based on the findings, ARMazing has proven to be an effective multimedia display medium that enhances attraction and interactivity at Bandung Techno Park while providing visitors with a more engaging educational experience.